Literacy Strengthening: A Case Study of Writing Class Program for Elementary School grade - Umi Farkhatun (Prodi PGMI IAIN Salatiga, 2020)
The low interest in reading Indonesian students as one of the literacy skills. As an alternative solution to this, effective literacy improvement programs are needed for elementary school students. This study aims to determine the method of child writer's class program as a program to strengthen children's literacy. The subjects were 20 child writer class participants. In this research, data was taken by a descriptive qualitative method. The object was from students who have in 7th and 11th years old. The program was done by organizes literacy activities such as seminars and writing training. Activities in this program emphasize a percentage of 30.0% of theoretical and 70.0% of writing practice. The results showed that the child in writing activity has strengthened literacy skills. It was caused because they understood the program. The program supported them to increase literacy skills especially writing. This is evidenced by the success of the program in publishing two anthology books written by 67 young writers.